Analysis of the sol and gel structures of potato starch over a wide spatial scale. Issue 9 (21st July 2021) - Nagasaki, Akane; Matsuba, Go; Ikemoto, Yuka; Moriwaki, Taro; Ohta, Noboru; Osaka, Keiichi
Abstract: We analyzed edible potato starch and observed the interaction between its granular structure and water molecules. We studied the changes caused by gelatinization during heating and stirring using microscopy, micro‐FT‐IR spectroscopy, and X‐ray scattering techniques. A wide range of spatial scales was revealed using these various techniques. The rate of gelatinization varied significantly and was dependent on the starch concentration. The process of adsorption of water on starch molecules was studied using the humidity‐controlled FT‐IR spectroscopy technique. Furthermore, by comparing the X‐ray scattering profiles of dry and wet granules, the 9‐nm repeat "cluster" structure was studied. A gradual collapse of the granules occurred during the processes of heating and stirring. A clustered smectic structure and a smectic‐like structure were observed in the opaque gel after gelatinization. Upon further heating, a transparent gel was obtained after the melting of the cluster. Abstract : We analyzed edible potato starch and observed the interaction between its granular structure and water molecules. A wide range of spatial scales was revealed using various techniques such as X‐ray scattering and FT‐IR measurements. We could succeed gelatinization and gelation process with a wide spatial scale.